2007
DOI: 10.1177/000313480707300823
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Malignant Melanoma of the Gallbladder Presenting as Biliary Colic: A Case Report and Review of Literature

Abstract: Malignant melanoma (MM) is the most common cancer to metastasize to the gastrointestinal tract. Autopsy reports estimate that up to 15 per cent of these patients also have gallbladder metastases, and MM accounts for up to 60 per cent of metastatic lesions to the gallbladder. However, despite its prevalence, MM to the gallbladder is reported only sparingly in the literature. This discordance may be explained by the fact that these lesions are seldom symptomatic. Abdominal ultrasound remains the modality of choi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…Examination of the GB revealed MM. In their review, the authors indicated that only 60 cases of MM had been reported in the world literature and 81% of patients had symptoms leading to a cholecystectomy [ 21 ]. Their analysis showed that while there is a concern for port-site involvement with a LC, this incidence might be similar in open cases [ 22 ].…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Examination of the GB revealed MM. In their review, the authors indicated that only 60 cases of MM had been reported in the world literature and 81% of patients had symptoms leading to a cholecystectomy [ 21 ]. Their analysis showed that while there is a concern for port-site involvement with a LC, this incidence might be similar in open cases [ 22 ].…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Their analysis showed that while there is a concern for port-site involvement with a LC, this incidence might be similar in open cases [ 22 ]. The authors concluded that while more studies were needed, LC is the strategy of choice for patients with localized disease [ 21 ].…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Involvement of the gallbladder seldom produces symptoms, but melanoma metastases in the gallbladder may rarely cause acute cholecystitis (Henriques 1955;Ostick and Haqqani 1976;Langley et al 1997) or masquerade cholelithiasis (Herrington 1965). 1964;Zemlyn 1966;Shimkin et al 1972;McFadden et al 1979;Bundy and Ritchie 1982;Murphy et al 1987;Stutte et al 1989;Goldin 1990;Hahn et al 1993;Avila et al 1994;Gawenda et al 1995;Abdelli et al 1996;Bedo et al 1996;Holloway and King 1997;Seelig and Schönleben 1997;Dong et al 1999;Hallal et al 1999;Paolini et al 1999;Cellerino et al 2000;Köhler et al 2000;Guida et al 2002;Gogas et al 2003;Crippa et al 2004;Gassler et al 2004;Uchikov et al 2004;Rehani et al 2006;Romero et al 2006;Varsamidakis et al 2006;Katz et al 2007;Marone et al 2007;Nelms et al 2007;Takayama et al 2007;Tuveri and Tuveri 2007;Samplaski et al 2008.…”
Section: Malignant Melanoma Metastatic To the Gallbladdermentioning
confidence: 99%
“…Selected References Pautler and Gallavan 1951;Henriques 1955;Kazmann 1956;Zemlyn 1966;Gabriele and Jouffre 1969;Shimkin et al 1972;McFadden et al 1979;Daunt and King 1982;Vantomme et al 1984;Murphy et al 1987;Agosti et al 1989;Stutte et al 1989;Goldin 1990;Avila et al 1994;Seelig and Schönleben 1997;Dong et al 1999;Cellerino et al 2000;Kohler et al 2000;Guida et al 2002;Gogas et al 2003;Crippa et al 2004;Gassler et al 2004;Swiatoniowski et al 2004;Rehani et al 2006;Romero et al 2006;Varsamidakis et al 2006;Katz et al 2007;Marone et al 2007;Nelms et al 2007;Tuveri and Tuveri 2007;Samplaski et al 2008;Hamodat and Alhumidi 2009;Matsubayashi et al 2012. As already mentioned above, the similarity of presentation renders the diagnosis of primary gallbladder melanoma vs. metastatic melanoma difficult in a proportion of the cases. Melanoma metastatic to the gallbladder can cause acute, obstructive cholecystitis (Henriques 1955;Ostick and Haggani 1976;Langley et al 1997;Vernadakis et al 2009) or masquerading as cholelithiasis (Herrington 1965).…”
Section: Differential Diagnosis: Malignant Melanoma Metastatic To Thementioning
confidence: 99%
“…Probably due to tumor necrosis and an associated inflammatory reaction, metastatic MM can cause, or be associated with, acute cholecystitis (Henriques 1955;Ostick and Haggani 1976;McFadden et al 1979;Bundy and Ritchie 1982;Bugnon et al 1987;Langley et al 1997;Vernadakis et al 2009). Similar to other gallbladder metastases, MM can cause gallbladder obstruction, sometimes inducing gallbladder colic (Paolini et al 1999;Ligeron-Esbrayat and Guillot 2002;Nelms et al 2007). The prognosis of metastatic MM to the gallbladder is poor, with a median survival time of 6-9 months (Langley et al 1997;Dong et al 1999;Katz et al 2007), but postcholecystectomy survival times of up to 13.5 months have been reported (Dong et al 1999).…”
Section: Malignant Melanomamentioning
confidence: 99%